Epitranscriptomic Analysis of m6A Methylome After Peripheral Nerve Injury - Zhang, Lei; Hao, Dingyu; Ma, Pengyi; Ma, Boyuan; Qin, Jia; Tian, Guangyuan; Liu, Zihao; Zhou, Xianhu (Frontiers in Genetics, 2021)
N6-methyladenosine(m6A) is one of the most plentiful internal RNA modifications, especially in eukaryotic messenger RNA (mRNA), which plays pivotal roles in the mRNA life cycle and nerve development processes. mRNA m6A methylation pattern in Peripheral Nervous Injury (PNI) has not been verified. In this study, samples were collected from Sciatic Nerve Injury (SNI) and control rats. m6A-related methyltransferases/demethylases were up-regulated after SNI by quantitative real-time PCR. High-throughput sequencing (MeRIP-seq) was performed to reveal the m6A methylation landscape. 4014 m6A peaks were significantly changed, including 2144 up-regulated and 1870 downregulated m6A peaks, which were corresponded to 1858 differentially genes. 919 significantly different genes were found by joint analysis of MeRIP-seq and RNA-seq. GO and KEGG pathway analyses were performed to probe these modified genes. Changed genes of m6A-modified transcripts were mainly related to the immune system process, cell activation, and nervous system development. KEGG pathway analyses highlighted the Cell cycle, B cell receptor signaling pathway, Axon guidance pathway, and Calcium signaling pathway. Moreover, autophagy was activated and autophagy-related gene atg7 increased in m6A methylation and protein expression level. These data further enrich the contents of epigenetics and may provide a new opinion to promote functional recovery in PNI.